An overview on phytochemical, anti-inflammatory and anti-bacterial activity of basella alba leaves extract - Abdul Kalam, Azad; Wan Sulaiman, Wan Mohd. Azizi; Z. M., Babar; Labu, Zubair Khalid; Zabin, S. (International Digital Organization for Scientific Information (IDOSI), 2013)
Inflammation is the complex biological response of vascular tissue to harmful stimuli such as pathogens, damaged cells, or irritants. In the present investigation an attempt was made to screen the anti-inflammatory activity of Basellaalba leaf. From this study, it can be concluded that, Basellaalba possesses a good anti-inflammatory activity. In the cotton pellet induced inflammation and In the carrageenan induced inflammation the animals treated with the plant extract have been shown a significant activity at 500 mg/kg dose (p<0.001) which was comparable with the standard drug. In view of the percentage inhibition also the plant was studied, in which the plant extract was found effective. The antibacterial activity was carried out using different dilutions of methanolic extract against gram positive strains (Staphylococcus aureus, Micrococcus luteus, Bacillus subtilus) and gram negative ones (Pseudomonas aeruginosa) by the cup-plate assay method and minimum inhibitory concentrations (MICs). The different concentrations of extract showed moderate activity against Pseudomonas aeruginosa, Bacillus subtiliswhile weak response against Staphylococcus aureus, Micrococcus luteus and Escherichiacoli. The minimum inhibitory concentration of methanolic extract was 6.25μg/ml against Staphylococcus aureus, Micrococcus luteus, Pseudomonas aeruginosa and Bacillussubtilus and 12.5 μg/ml against Escherichia coli. The overall result of this study indicates that the methanolic extract of Basellaalba have interesting anti-inflammatory and antibacterial properties.